Peran Teknologi Finansial dalam Meningkatkan Efisiensi Jumlah Uang Beredar di Indonesia - Fadhila Meliyanti; Ratu Habibah; Puput Febrianty; Rasidah Novita Sari (Universitas Katolik Widya Karya Malang, 2023)
This research aims to analyze the role of financial technology in increasing the efficiency of the money supply in Indonesian. This research uses a qualitative approach by explaining to readers the role of technology in the amount of money in circulation, and by collecting data, comparisons, and the influence of financial technology in increasing the amount of money in circulation from a global perspective from literature and other sources that support and are related to our research.